2023
DOI: 10.1002/cmdc.202300258
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Assemblies for Cancer Therapy

Abstract: Supramolecular assemblies made by the self‐assembly of peptides are finding an increasing number of applications in various fields. While the early exploration of peptide assemblies centered on tissue engineering or regenerative medicine, the recent development has shown that peptide assemblies can act as supramolecular medicine for cancer therapy. This review covers the progress of applying peptide assemblies for cancer therapy, with the emphasis on the works appeared over the last five years. We start with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 145 publications
0
6
0
Order By: Relevance
“…Peptide assemblies have emerged as a new class of biomaterials and have received increased research attention over the last two decades. Since the seminal works demonstrated the applications of peptide assemblies in tissue engineering , and the report of exceptional self-assembling ability of short peptides, peptide assemblies have been explored for a wide range of applications, such as drug delivery, cancer therapy, optoelectronics, cell cultures, , antibacterial, immunomodulation, molecular imaging, , and protein mimics. , Being encouraged by these rapid advances, we and Ulijn et al have shown the use of enzymatic reactions for generating peptide assemblies as a type enzyme-responsive biomaterials. Specifically, we have been developing phosphopeptides as substrates of alkaline phosphatase (ALP) to generate peptide assemblies inside cancer cells as an alternative approach to target drug-resistant and immunosuppressive tumors . Recently, we have found that a phosphopentapeptide [NBD-LLLL- p Y ( 1 )] is able to undergo enzyme-instructed self-assembly (EISA) ,, and accumulate intranuclearly for killing cells that overexpress ALP, such as human induced pluripotent stem cells (iPSC) or osteosarcoma cells (e.g., Saos2) .…”
Section: Introductionmentioning
confidence: 99%
“…Peptide assemblies have emerged as a new class of biomaterials and have received increased research attention over the last two decades. Since the seminal works demonstrated the applications of peptide assemblies in tissue engineering , and the report of exceptional self-assembling ability of short peptides, peptide assemblies have been explored for a wide range of applications, such as drug delivery, cancer therapy, optoelectronics, cell cultures, , antibacterial, immunomodulation, molecular imaging, , and protein mimics. , Being encouraged by these rapid advances, we and Ulijn et al have shown the use of enzymatic reactions for generating peptide assemblies as a type enzyme-responsive biomaterials. Specifically, we have been developing phosphopeptides as substrates of alkaline phosphatase (ALP) to generate peptide assemblies inside cancer cells as an alternative approach to target drug-resistant and immunosuppressive tumors . Recently, we have found that a phosphopentapeptide [NBD-LLLL- p Y ( 1 )] is able to undergo enzyme-instructed self-assembly (EISA) ,, and accumulate intranuclearly for killing cells that overexpress ALP, such as human induced pluripotent stem cells (iPSC) or osteosarcoma cells (e.g., Saos2) .…”
Section: Introductionmentioning
confidence: 99%
“…20–24 These hydrogels have a wide range of applications in the biomedical field, such as sustained release of drugs and important biomolecules, 25–28 drug delivery, 25,29 cell culture, 27 tissue engineering, 1,29 wound healing, 19,32 and antimicrobial, 30–40 antiparasitic 37,42 and anticancer agents. 41–48 The self-assembled nanostructures show a remarkably increased bioactivity compared to the unassociated peptide molecules.…”
Section: Introductionmentioning
confidence: 99%
“…sPDCs typically include a small molecule prodrug as a hydrophobic block attached to a more hydrophilic and (typically) β-sheet-forming peptide to yield an amphiphilic molecular design; the prodrug motif promotes hydrophobic association of the resulting amphiphilic molecules in aqueous environments and contributes to the self-assembly of precise nanostructures . The most commonly produced nanoforms are high aspect-ratio one-dimensional nanofibers, which may further engage in physical entanglements to form hydrogels useful as localized drug delivery depots. , The enhanced therapeutic potential of sPDCs has been increasingly appreciated, , and exciting recent advances are sPDC formulations that codeliver both chemotherapies and immunotherapies, , sPDCs that gel in situ on contact with physiological environments, and the potential to incorporate bioactive targeting and therapeutic functionalities, such as through integrin or collagen binding peptide sequences, , and DNA aptamers . Accordingly, sPDC materials constitute a growing class of peptide-based materials being explored for applications in drug delivery …”
Section: Introductionmentioning
confidence: 99%